Conflict resolution between parent-child in the context of coach-athlete relationships among selected college athletes and their parents in the Greater Manila area - Ongcuango, Maria Elisha Gabrielle Bautista 1996-; Padilla, Monica Ceniza (2017)
"This study examined the communication and coaching interactions between the duality of role of selected Parent-Coach and Child-Athlete in the Greater Manila Area (GMA). This involved the following Parent-Coach Negotiation Points during the communication process with the Child-Athlete: (1) Athletic Goal, (2) Competition Choices, (3) Instructional Strategy, and (4) Motivational Strategy. Using a qualitative approach, the researchers conducted focus interviews with five (5) successful pairs of Parent-Coach and Child-Athlete and another five (5) unsuccessful pairs from a pool of informants in the Greater Manila Area. The study used the Co-orientation theory of Meleod and Chaffee (1973) in order to explain how the Parent-Coach and Child-Athlete communicate and negotiate to arrive at a certain outcome. In addition, the Thomas-Kilman Model of Conflict Resolution was used to assess the individual's behavior when the concerns of the Parent-Coach and Child-Athlete seem to be incompatible. Results have shown that the need for both parties to communicate is necessary in order to properly address instructions, observations and evaluation of performance. When conflicts arise between the parties, the Parent-Coach uses collaboration strategies in order find a solution that will fully satisfy both parties. On the other hand, the Child-Athlete uses compromising as a negotiation strategy to maintain harmony between them and their Parent-Coach."